MARKETING COMMUNICATION PT BODDIA JAYA DALAM MENGGAET FUNDING LUAR NEGERI - Ramsiah Tasruddin; Usti Arung Sari (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
This study aims to understand PT.Boddia Jaya's marketing communication model in attracting foreign parties. In addition, it is also to find out the obstacles experienced by PT.Boddia Jaya's company when communicating with foreign parties. The source of research data is the marketing division, Quality Control, and Front Desk of PT.Boddia Jaya. Data collection techniques namely observation and interviews. The results of research conducted at PT. Boddia Jaya can be concluded that there are three marketing communication strategies for foreign parties, namely Advertising, Advertising (by email) and Packaging (packaging). The strategy carried out by this company has been around since it first exported abroad. Even so, the three strategies that were carried out in establishing cooperation between PT.Boddia Jaya with foreign parties also experienced obstacles in communication. This is due to cultural and linguistic differences and also the great distances that make marketing communication between the two parties ever hampered. To overcome these obstacles, both parties learn each other's language and culture.